A New Perspective on the Pathophysiology of Idiopathic Intracranial Hypertension: Role of the Glia-Neuro-Vascular Interface - Eide, Per Kristian; Hansson, Hans-Arne (Frontiers in Molecular Neuroscience, 2022)
Idiopathic intracranial hypertension (IIH) is a neurological disease characterized by symptoms and signs of increased intracranial pressure (ICP) of unknown cause. Most attention has been given to the role of cerebrospinal fluid (CSF) disturbance and to intracranial venous hypertension caused by sinus vein stenosis. We previously proposed that key pathophysiological processes take place within the brain at the glia-neuro-vascular interface. However, the relative importance of the proposed mechanisms in IIH disease remains unknown. The aim of modern treatment regimens is to reduce intracranial CSF and venous pressures, but a substantial proportion of patients experience lasting complaints. Since 2010, the first author established a database for prospective collection of information from individuals being assessed for IIH. The database incorporates clinical, imaging, physiological and biological data, and information about treatment/outcome. The present study retrieved information from the database, asking the following research questions: In IIH subjects responding to shunt surgery, what is the occurrence of signs of CSF disturbance, sinus vein stenosis, intracranial hypertension, and microscopic evidence of structural abnormalities at the glia-neuro-vascular interface? Secondarily, do semi-quantitative measures of abnormal ultrastructure at the glia-neurovascular differ between subjects with definite IIH and non-IIH (reference) subjects? The study included 13 IIH patients who fulfilled the diagnostic criteria and who improved following shunt surgery, i.e. patients with definite IIH. Comparisons were done regarding magnetic resonance imaging (MRI) findings, pulsatile and static ICP scores and immune-histochemistry microscopy. Among these 13 IIH subjects, 6/13 (46%) patients presented with magnetic resonance imaging (MRI) signs of CSF disturbance (empty sella and/or distended perioptic subarachnoid spaces), 0/13 (0%) IIH patients had MRI signs of sinus vein stenosis, 13/13 (100%) IIH patients presented with abnormal preoperative pulsatile ICP [overnight mean ICP wave amplitude (MWA) above thresholds], 3/13 (23%) patients showed abnormal static ICP (overnight mean ICP above threshold), and 12/13 (92%) IIH patients showed abnormal structural changes at the glia-neuro-vascular interface. Comparisons of semi-quantitative structural variables between IIH and 12 age and gender matched reference (REF) subjects showed in IIH abnormalities in glial cells, neurons and capillaries. The present data suggest a key role of disease processes affecting the glia-neuro-vascular interface.